Mass spectrometry‐based top‐down and bottom‐up approaches for proteomic analysis of the Moroccan Buthus occitanus scorpion venom. Issue 7 (28th May 2021) - Daoudi, Khadija; Malosse, Christian; Lafnoune, Ayoub; Darkaoui, Bouchra; Chakir, Salma; Sabatier, Jean‐Marc; Chamot‐Rooke, Julia; Cadi, Rachida; Oukkache, Naoual
Abstract : Buthus occitanus (B. occitanus) is one of the most dangerous scorpions in the world. Despite the involvement of B. occitanus scorpion in severe cases of envenomation in Morocco, no study has focused yet on the proteomic composition of the Moroccan B. occitanus scorpion venom. Mass spectrometry‐based proteomic techniques are commonly used in the study of scorpion venoms. The implementation of top‐down and bottom‐up approaches for proteomic analyses facilitates screening by allowing a global view of the structural aspects of such complex matrices. Here, we provide a partial overview of the venom of B. occitanus scorpion, in order to explore the diversity of its toxins and hereafter understand their effects. To this end, a combination of top‐down and bottom‐up approaches was applied using nano‐high liquid chromatography coupled to nano‐electrospray tandem mass spectrometry (nano‐LC‐ESI MS/MS). The LC‐MS results showed that B. occitanus venom contains around 200 molecular masses ranging from 1868 to 16 720 Da, the most representative of which are those between 5000 and 8000 Da. Interestingly, combined top‐down and bottom‐up LC‐MS/MS results allowed the identification of several toxins, which were mainly those acting on ion channels, including those targeting sodium (NaScTxs), potassium (KScTxs), chloride (ClScTxs), and calcium channels (CaScTx), as well as antimicrobial peptides (AMPs), amphipathic peptides, myotropic neuropeptides, and hypothetical secreted proteins. This study reveals the molecular diversity of B. occitanus scorpion venom and identifies components that may have useful pharmacological activities. Abstract : Buthus occitanus scorpion possesses highly toxic venom. This article describes the first proteomic screening of the Moroccan B. occitanus venom. Our findings highlight the complexity and the toxin diversity of this venom. The most representative compounds are neurotoxins. In addition, antimicrobial peptides, amphipathic peptides, myotropic neuropeptides, and hypothetical secreted proteins were also detected in this venom.